Geoelectrochemical CO production: Implications for the autotrophic origin of life - Kitadai, Norio (Sci Adv, 2018)
Wächtershäuser’s proposal of the autotrophic origin of life theory and subsequent laboratory demonstrations of relevant organic reactions have opened a new gate for the exploration of the origin of life. However, this scenario remains controversial because, at present, it requires a high pressure of CO as a source of carbon and reducing energy, although CO must have been a trace C species on the Hadean Earth. We show that, simulating a geoelectrochemical environment in deep-sea hydrothermal fields, CO production with up to ~40% Faraday efficiency was attainable on CdS in CO(2)-saturated NaCl solution at ≤–1 V (versus the standard hydrogen electrode). The threshold potential is readily generated in the H(2)-rich, high-temperature, and alkaline hydrothermal vents that were probably widespread on the early komatiitic and basaltic ocean crust. Thus, Wächtershäuser’s scenario starting from CO(2) was likely to be realized in the Hadean ocean hydrothermal systems.